The IPNU The IPNU - Ibad, Muhammad Badrul Munir (SETYAKI : Jurnal Studi Keagamaan Islam, 2023)
Abstract: The branch leadership of the Nahdlatul Ulama Student Association in Majalengka Regency is a forum for the struggle of Nahdlatul Ulama students to promote commitment to Islamic values, scholarship, cadre, and nationality in an effort to develop their abilities for the upholding of Islamic teachings in the Ahlussunnah Wal-Jama'ah style. The purpose of this research is to find out the strategy formulation, implementation and evaluation of strategies carried out by the Majalengka Regency IPNU Branch Management in instilling the Ahlussunnah Wal Jama'ah understanding to students. The theory used in this study is Fred R. David's communication strategy theory about strategic management which consists of three stages, namely strategy formulation, strategy implementation and strategy evaluation. In this study it was stated that the Management of the Majalengka Regency IPNU Branch carried out the formulation of a target identification strategy targeting students and santri, compiling messages using the one side issue method so that students and santri were interested and felt comfortable with IPNU. Keywords: Aswaja, IPNU, Communication